Brefeldin A variant via combinatorial screening acts as an effective antagonist inducing structural modification in EPAC2. Issue 17 (22nd November 2022) - Uttarkar, Akshay; Niranjan, Vidya
ABSTRACT: Drug discovery can be impactful with re-purposing and combinatorial strategies leading to potential pharmaceutical outputs. EPAC isoform inhibition is crucial in vascular functions to prevent chronic inflammation leading to hypertension and myocardial infarction. Current drugs fail to induce a conformational change in EPAC isoforms. An attempt utilising brefeldin A, a natural inhibitor was subjected to a substitution of 3 side-chain groups with 43 fragments via combinatorial strategy. This resulted in generating a library of 79, 507 brefeldin A variants. High throughput virtual screening yielded 68, 043 variants followed by precision docking providing 117 lead-like brefeldin A variants. The best-docked variant labelled as BrefA1 has increased binding efficiency of −10.841 kcal/mol compared to cAMP2 (positive control) with −10.692 kcal/mol. Simulation studies up to 200 ns of complex lead to re-orientation of target tertiary structure resulted in RMSD change of 30.221 Å, suggesting the EPAC2 structure modification leading to unavailability of RAS-GEF domain and its interaction with Rap1b. To identify the new conformation of EPAC2 single domain antibody was designed to bind specifically to re-structured EPAC2 for potential identification over the native target structure. The resulting Brefeldin variant can be potentially labelled as the most effective antagonist against EPAC2 which induces theoretically irreversible structural re-conformation.